Relationship between Population Growth and Urbanization - Novák, Norbert (International Journal of Engineering and Management Sciences, 2020)
The main purpose of this article is to examine how to respond to and change the field of urbanization. Creating dwindling new opportunities and challenges for globalization, new sector introductions and agricultural dominance. In relation to changing trends in urban and rural environments, people’s preferences are very diverse and their lives are changing. The difference between a big city and a small city can test different lifestyles. It is a fundamentally important infrastructure personality insurance system (both cities), important from the point of view of larger cities and very different from small towns in terms of quality. The benefits of small towns can be a unique lifestyle and a healthy lifestyle, which can certainly be felt. Among the different characteristics of urbanization in developing and developed countries, we can mention the different time course and magnitude [1]. Namely, in developed countries the urban explosion has taken place for a long time and with fewer people than in developing countries [2]. The rate of urban population growth in the latter group will be 4.04% between 1950 and 1975, 3.6% between 1975 and 2000, and 2.4% between 2000 and 2030. The Earth and all of humanity are facing many challenges these days, and this trend will continue in the future. The planet’s overpopulation and changing eating habits put great pressure on agriculture and the countryside. Research focused on the countryside focuses on analyzing the various functions of rural areas.